1999
DOI: 10.1086/306681
|View full text |Cite
|
Sign up to set email alerts
|

Global VLBI Observations of the Compact OH Megamaser Emission from III Zw 35 and IRAS 17208−0014

Abstract: We have performed global VLBI observations of the OH megamaser galaxies III Zw 35 and IRAS 17208[0014. We detect strong and compact 1667 MHz OH emission from each galaxy, but, apart from one weak detection of a single 1665 MHz OH feature in III Zw 35, no 1665, 1720 MHz, or continuum emission are detected, which indicates that they occur on size scales greater thanWe surmise that 0A .1. the OH emission consists of two components. One is di †use, has unsaturated masers pumped by farinfrared radiation, and is rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 21 publications
8
55
1
Order By: Relevance
“…Similar observations of halos for other maser species have been reported in the last years. This phenomenon has been seen in OH megamasers (Diamond et al 1999), in OH masers in supernova remnants (Claussen et al 1999), in SiO masers in circumstellar envelopes (Greenhill et al 1995), in galactic H 2 O masers (Gwinn 1994) and in 25 GHz methanol masers (Sobolev et al 1998). In addition to these results, Moscadelli et al (1999) observed in W 3(OH) that a large amount of flux density was missing in the crosspower spectrum of the 12.2 GHz methanol masers.…”
Section: Summary Of the Resultsmentioning
confidence: 62%
“…Similar observations of halos for other maser species have been reported in the last years. This phenomenon has been seen in OH megamasers (Diamond et al 1999), in OH masers in supernova remnants (Claussen et al 1999), in SiO masers in circumstellar envelopes (Greenhill et al 1995), in galactic H 2 O masers (Gwinn 1994) and in 25 GHz methanol masers (Sobolev et al 1998). In addition to these results, Moscadelli et al (1999) observed in W 3(OH) that a large amount of flux density was missing in the crosspower spectrum of the 12.2 GHz methanol masers.…”
Section: Summary Of the Resultsmentioning
confidence: 62%
“…VLBI observations have mapped the OHM emission for a handful of nearby galaxies (Yates et al 2000;Pihlström et al 2001Pihlström et al , 2005Klöckner et al 2003;Lonsdale et al 2003;Rovilos et al 2003;Klöckner & Baan 2004;Richards et al 2005;Momjian et al 2006), showing that the difference in apparent optical depth between the entire galaxy and the brightest individual maser spots varies by as much as Δτ 1-4. Furthermore, the gain for individual maser spots with cloud-cloud overlap can be as high as several hundred (e.g., III Zw 35; Diamond et al 1999;Parra et al 2005), compared to the diffuse background. Since high-resolution OH maps do not exist for the vast majority of the IRS galaxies, however, we use τ app 1667 while remaining mindful of the above caveats.…”
Section: Comparing Observations and Theorymentioning
confidence: 99%
“…Powerful OH maser emission has been previously detected in the circumnuclear disk of Arp220, IIIZw35, Mrk273, and IRAS17208-0014 by Lonsdale et al (1998), Diamond et al (1999), Yates et al(2000), and Diamond et al(1999), respectively. Previous VLBI observation and time series analysis of the spectra (Haschick, Bann & Peng 1994) suggests that the masers originate in a rotating torus surrounding a massive object (with a mass M of 1.5 x 10 r M 0 ) at the center of the galaxy (Watson & Wallin 1994).…”
Section: Introductionmentioning
confidence: 87%